Salix_herbacea - Armbruster, Georg F.J.; Gielly, Ludovic; Taberlet, Pierre; Stöcklin, Jürg (Dryad Digital Repository, 2011)
AFPL data: Matrix with samples (rows) and markers (columns), 1 indicates presence of AFLP-fragments, 0 indicates absence of AFLP-fragments